1999
DOI: 10.1017/s0265051799000212
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic education and the practice of music teaching

Abstract: Over the past three decades it has become customary to regard music education as a form of aesthetic education. Recently a number of writers have expressed some objections to this view which they maintain has acquired the status of an accepted orthodoxy. In a healthy educational climate it is right that any orthodoxy should be questioned and aesthetic education has often become the subject of an international debate The purpose of this paper is not to add another voice to that debate but to re-examine the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 3 publications
0
9
0
6
Order By: Relevance
“…Bentuk musik dapat dibedakan atas tiga macam, yaitu musik vokal, musik instrumental, dan musik campuran dalam konteks pembelajaran tematik di Sekolah Dasar dalam hubungannya pula dengan memasukkan materi lewat bernyanyi atau nyanyian menggunakan lagu-lagu yang sesuai tema pembelajaran menjadi terasa sangat penting perlu dikembangkan dari aspek sisi terwujudnya lagu yang sesuai dengan isi dari materi ajar tersebut. Plummeridge (1999) pemahaman mendasar berkait dengan lagu yang perlu diketahui adalah apa yang dilihat sebagai produk tidak lebih penting dari proses karena sebuah proses berlagu akan berimplikasi pada banyak aspek termasuk aspek masuknya materi ajar dengan cara yang lebih efektif.…”
Section: Pembahasan Tentang Kebutuhan Dan Pengembangan Materi Ajar Muunclassified
See 1 more Smart Citation
“…Bentuk musik dapat dibedakan atas tiga macam, yaitu musik vokal, musik instrumental, dan musik campuran dalam konteks pembelajaran tematik di Sekolah Dasar dalam hubungannya pula dengan memasukkan materi lewat bernyanyi atau nyanyian menggunakan lagu-lagu yang sesuai tema pembelajaran menjadi terasa sangat penting perlu dikembangkan dari aspek sisi terwujudnya lagu yang sesuai dengan isi dari materi ajar tersebut. Plummeridge (1999) pemahaman mendasar berkait dengan lagu yang perlu diketahui adalah apa yang dilihat sebagai produk tidak lebih penting dari proses karena sebuah proses berlagu akan berimplikasi pada banyak aspek termasuk aspek masuknya materi ajar dengan cara yang lebih efektif.…”
Section: Pembahasan Tentang Kebutuhan Dan Pengembangan Materi Ajar Muunclassified
“…Wujud karya musik dalam praktik pembelajarannya di sekolah selain ditujukan untuk mendapatkan pengalaman estetik siswa, melalui proses berkesenian juga diarahkan untuk menyampaikan pesan pendidikan. Penyampaian pesan pendidikan ini lebih kehubungan dengan pengolahan informasi melalui kegiatan berkesenian (Tomlinson, 2012;Plummeridge, 1999) dan itu yang dipraktekkan dalam pendidikan seni musik pada Pendidikan Dasar saat ini.…”
Section: Pembahasan Tentang Kebutuhan Dan Pengembangan Materi Ajar Muunclassified
“…This broad term covers criticism and philosophical aesthetics. The question of the relation of these will be discovered with reference to Osborne (1979), Plummeridge (1999), Kimmel (1992, Sim (1992), Hanfling (1995), Senyshyn (1996) and Rowe (2000). The former concerns an individual's response to a performance; the latter is a second order discipline which analyses the language of criticism.…”
Section: (D)mentioning
confidence: 99%
“…The debate became fierce and filled with mutual misunderstandings and accusations, which indicated that very important ideological questions were at stake. Some writers intervened, trying to sketch an intermediate position that retains both the music as aesthetic and as a practice (Constantin Koopman, 1998; Charles Plummeridge, 1999). Readers are referred to these clarifying contributions.…”
Section: Music Education As Aesthetic Education (Meae)mentioning
confidence: 99%